Shifts in Bird Migration Timing in North American Long-Distance and Short-Distance Migrants Are Associated with Climate Change - Zaifman, Jay; Shan, Daoyang; Ay, Ahmet; Jimenez, Ana Gabriela (International Journal of Zoology, 2017)
Bird migration is a synchronized event that has evolved over thousands of years. Changing temperatures due to climate change threaten the intricacies of migration timing for birds; however, the extent of these changes has only recently begun to be addressed. Utilizing data from the citizen-science website eBird and historical temperature data, we analyzed bird migration timing in two states warming quickly (Alaska and Maine) and one warming gradually (South Carolina). Using linear regressions, we looked at relationships between different temperature indices and year with bird migration timing from 2010 to 2016. Bird migration through all three states, regardless of warming rate, showed similar rates of alterations. Additionally, in every state over half of the birds that had altered migration timing were long-distance migrants. Furthermore, we performed feature selection to determine important factors for changing migration timing of birds. Changes to summer resident and transient bird migration were most influenced by state. In winter resident migration, departure date and length of stay were most influenced by maximum temperature, while arrival date was most associated with minimum temperature. Relationships between changing temperatures and migration timing suggest that global climate change may have consequential effects on all bird migration patterns throughout the United States.